Pengaruh Harga, Kualitas Barang Dan Brand Image Terhadap Keputusan Pembelian Konsumen Di Toko Andre Sabungan - Nasution, Meisa Fitri; Febriani, Budi (Jurnal Manajemen Akuntansi (JUMSI), 2022)
A business that is quite in demand is the clothing business. The need for clothing today is very important for humans. A person can look fashionable and more confident if they wear good clothes. In Indonesia, the fashion business is growing rapidly, as seen from the many stores and distributions that sell various kinds of clothing. Along with the development of the type of clothing, the competition for profits and customers is also increasing. Toko Andre is a type of trading business engaged in fashion and household needs, where this store sells women's, men's and children's clothing also sells other household needs, this study focuses on fashion. This business has many competitors with the same type of business, for it to influence consumer purchasing decisions is very necessary in the progress of this business, Andre stores must pay attention to how to attract consumers. Researchers see that there are several things that need to be considered to attract consumers, so that consumer purchasing decisions become more improved, such as price, product quality and brand image. These factors can be used as a strategy to improve consumer purchasing decisions in the face of competition and the sustainability of Andre's store business during this pandemic, especially.